Strengthening Entrepreneurship Characteristics in the Effort of Increasing MSMe Performance Through Management Ability and Entrepreneurship Competence - Dian Triyani; Edy Mulyantomo; Rr. Lulus Prapti Nugroho Setiasih Surjanti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
MSME is a form of business carried out by micro, small and medium scale business actors. The development and growth of MSMEs contribute to the economy of a region so that efforts are needed that lead to improving the performance of MSMEs. Likewise, traditional food MSMEs in Bendungan Village, Gajahmungkur District, Semarang, which have contributed to absorbing labor in the field of entrepreneurship. Related to the above, this study aims to analyze (1) the effect of entrepreneurial characteristics on management ability, (2) the effect of entrepreneurial characteristics on entrepreneurial competence, (3)the influence of entrepreneurial characteristics on the performance of SMEs,(4)influence management ability ton the performance of SMEsAnd(5)influence of entrepreneurial competence ton the performance of SMEs. The research population is MSME actors who do business in the field of traditional food in the Bendungan Village, Gajahmungkur District, Semarang City. This study used 88 data from MSME respondents who came from the answers to the questionnaire. The analysis tool uses Partial Least Square (PLS). The results of the study show that entrepreneurial characteristics influence management ability, entrepreneurial competence and MSME performance. Furthermore, management capabilities and entrepreneurial competencies are proven to be able to improve MSME performance.